2015
DOI: 10.1111/hdi.12369
|View full text |Cite
|
Sign up to set email alerts
|

Changes in biochemical, hemodynamic, and dialysis adherence parameters in hemodialysis patients during Ramadan

Abstract: This paper aimed to study the effect of Ramadan fasting on biochemical and clinical parameters and compliance for dialysis. A prospective multicenter observational cross-sectional study comparing fasting with a non-fasting stable adult hemodialysis patients for demographic and biochemical parameters, compliance with dialysis, inter-dialytic weight gain, pre- and post-blood pressure, and frequency of intradialytic hypotensive episodes was carried out. Six hundred thirty-five patients, of whom 64.1% fasted, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 12 publications
6
18
0
Order By: Relevance
“…After controlling for within person variation, sociodemographic and significant comorbidities (diabetic and hypertension status), we found no clinically significant differences between Ramadan fasting groups in means of the majority of biochemical variables including serum albumin, creatinine, blood urea nitrogen, phosphorus, calcium, sodium, hemoglobin, erythrocytes count, and platelets count. This accord with the findings of prior studies suggesting that, on average, Ramadan fasting by hemodialysis patients is not associated with significant clinical changes in key biochemical parameters [3, 21, 24]. The current study found that RFG and RPFG had slightly higher mean IDWG by 0.6 kg and 0.4 kg than RNFG, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…After controlling for within person variation, sociodemographic and significant comorbidities (diabetic and hypertension status), we found no clinically significant differences between Ramadan fasting groups in means of the majority of biochemical variables including serum albumin, creatinine, blood urea nitrogen, phosphorus, calcium, sodium, hemoglobin, erythrocytes count, and platelets count. This accord with the findings of prior studies suggesting that, on average, Ramadan fasting by hemodialysis patients is not associated with significant clinical changes in key biochemical parameters [3, 21, 24]. The current study found that RFG and RPFG had slightly higher mean IDWG by 0.6 kg and 0.4 kg than RNFG, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…The present study found a significant increase in mean serum potassium in RFG than that of RNFG suggesting that hemodialysis patients fasting daily during Ramadan may be at risk of hyperkalemia. Although, this finding differs from some previous studies [3, 21–24], which showed no significant changes in serum potassium due to Ramadan fasting in hemodialysis patients, it is consistent with the findings of another study from KSA by Al-Khader and colleagues [20]. However, no adverse effects related to hyperkalemia were reported by that study [20].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The findings from several studies in Saudi Arabia report that poor nutritional status and high prevalence of malnutrition (among HD patients) are consistent with these observations [23,26,27]. In HD patients, changes in various clinical and biochemical parameters during R have been reported in relatively few studies, and generally no adverse effects have been noted [7,8,28]. The impact or association of any nutritional changes with changes in anthropometric or blood chemistry (including lipids) is largely unexplored.…”
Section: Introductionsupporting
confidence: 52%